Uptake of Breast Screening Among Female Staff at A Tertiary Health Institution in South-West Nigeria - E. ADETONA, Adesoji; O. OSUNGBADE, Kayode; O. AKINYEMI, Oluwaseun; A. OBEMBE, Taiwo (Journal of Preventive Medicine And Care, 2021)
Background Breast cancer is one of the most common types of cancer affecting women globally. It has shown increasing morbidity and mortality rates over the past years. Several screening methods ranging from simple breast self-examination to a highly sensitive test procedures for early detection and treatment are available, but uptake is a challenge. Lack of a national screening programme in the country makes available regional screening programme unsuccessful. This study aims to assess the factors affecting the uptake of breast cancer screening programme among female staff in a tertiary hospital, Southwest Nigeria. Method This descriptive cross-sectional study involves 375 participants selected by a stratified random sampling technique, with proportional allocation to population size and the use of a semi-structured questionnaire. Respondents were questioned on their basic knowledge of breast cancer symptoms, risk factors and treatment, over a score of 50 and above, were set as the cut-off mark to determine good knowledge of breast cancer. Patients attitudes towards breast cancer screening as well as factors affecting uptake were also measured. Descriptive statistical analysis was done using SPSS-20 while the predictors of the uptake of screening were determined using logistic regression at p ≤ 0.05. Results There were 360 respondents, comprising of 13.3% clinical and 86.7% non-clinical female staff within the age bracket of 20 to 58 years (38.2±0.42 years). Out of the respondents, 97.8% have heard about breast cancer but only 52.3% had been screened while 65.5% had “Good knowledge” of breast cancer. Positive attitude to breast cancer screening was displayed in 52.5% while over 90% claimed to be practicing breast self-examination. Only 36.1% of respondents above 40 years old have had mammography done. Most frequent barriers to screening uptake include cost, poor accessibility to screening facilities, shyness (unfamiliar screener), unavailability of female doctors, careless attitude, fear of cancer and other more pressing family problems. Using logistic Regression at p ≤ 0.05, females with a negative attitude, young unmarried (less than 30years) and lack of easy accessibility to screening facilities were significant factors affecting uptake of breast cancer screening services. Conclusion Due to knowledge-uptake gap of breast cancer screening revealed in this study. It is therefore obvious from these findings that a concerted effort is needed to actively remove these barriers by repeated education, training and re-training strategies among health workers and to improve their uptake and level of advocacy and campaign for breast cancer screening among their patients and clients.
Keywords: Breast Cancer; Screening; Female health workers.